2014
DOI: 10.1149/2.016405jss
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al3+Doping into the Zr4+Site on the Photoluminescence Properties of Ca3-xEuxZrSi2O9+x/2Phosphors

Abstract: Red-emitting Ca3−xEuxZr1−yAlySi2O9+(x−y)/2 (0.05 ≤ x ≤ 0.25, 0 ≤ y ≤ 0.07) phosphors were synthesized in a single phase form by the conventional solid-state reaction method and their photoluminescence properties were characterized. The charge-transfer efficiency from O2− to Eu3+ was controlled by the Al3+ doping into the Zr4+ site in the host Ca3ZrSi2O9 lattice, which resulted in the successful enhancement of the luminescent emission intensity of these phosphors. The highest emission intensity was obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Hence, only tetragonal phase can be stabilized at room temperature by doping undersized Al 3+ ions in the zirconia nanocrystals. 10,11,56 One of the objectives of this paper is also to study the ZrO 2 layer thickness on the stabilization of the high temperature tetragonal phase. For that particular purpose multilayers consisted of alternate layers of ZrO 2 and Al 2 O 3 at different zirconia layer thicknesses (15 and 7 nm) has been synthesized keeping the thickness of the alumina layers same.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, only tetragonal phase can be stabilized at room temperature by doping undersized Al 3+ ions in the zirconia nanocrystals. 10,11,56 One of the objectives of this paper is also to study the ZrO 2 layer thickness on the stabilization of the high temperature tetragonal phase. For that particular purpose multilayers consisted of alternate layers of ZrO 2 and Al 2 O 3 at different zirconia layer thicknesses (15 and 7 nm) has been synthesized keeping the thickness of the alumina layers same.…”
Section: Resultsmentioning
confidence: 99%
“… 12 In order to further enhance the emission efficiency, Zuo et al tried to partially substitute Zr 4+ ions with Al 3+ ions in the host Ca 3 ZrSi 2 O 9 , and finally the inner quantum yield was increased to 46%. 13 This enhancement was mainly ascribed to the charge compensation effect, which is helpful for improving the crystallinity of the phosphors. However, the relatively low quantum yield still limits its practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such phosphors with the layered structure would be resistant to the concentration quenching, even if a large amount of activator was introduced into the host lattice. Considering this, our research group has successfully synthesized several novel phosphors with layered structure, and has revealed that these layered compounds are suitable for host materials of phosphors with high luminescent property [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%